Determinant of Teenage Pregnancies (KEMAS: Jurnal Kesehatan Masyarakat, 2017)
The number of teenage pregnancies in Banyumas district in 1727 as a pregnant teenager  less than 20 years old and young teenagers maternity by 1382 either through premarital or marital. The research was conducted in 2016 aimed to determine the factors that affect pregnancy young age in Banyumas. This research is a quantitative research with cross sectional approach. The population was all pregnant women under 20 years of pregnancy and childbirth are recorded in the data in Puskesmas Jatilawang, Puskesmas I Cilongok, health center II Donates totaled 614 people. Calculation of the estimated proportion of the sample using the formula obtained 107 samples, taken using simple random sampling technique. The data collection is done by using a questionnaire that advance has been tested questionnaire to meet the validity and reliability of a measuring instrument. Yan data analysis used univariate analysis with descriptive statistics, bivariate analysis using chi square, and multivariate analysis by logistic regression. The results showed the level of education, marital status, knowledge, access to information, health care utilization, the role of the family has no effect on pregnancy young age. Attitudes and access to health information is the most dominant variable affecting the pregnancy young age.